Detection of Chili Powder Adulteration with Rhodamine B in Traditional Markets of Singosari District Using Fourier Transform Infrared (FT-IR) Spectroscopy and Chemometrics: Detection of Chili Powder Adulteration with Rhodamine B - Putri, Anggita (Brawijaya University, 2024)
Introduction: Chili powder (Capsicum annum L.) is a spice that has many benefits, one of which is as a Chilli powder (Capsicum annuum L.) is a spice that has many benefits, one of which is as a cooking ingredient, a natural red dye, and a traditional medicinal ingredient. The high demand for chili, the short shelf life, and the fluctuations in chilli prices have led to the adulteration of chilli powder with economic motives, namely with Rhodamin B. RI regulation No. 239/Men.Kes/Per/85 states that Rhodamin B is a dangerous color substance and is prohibited from use in drugs, food, and cosmetics. Objectives: This study aims to determine whether there are adulterated chili powder products in the Traditional Market of Singosari District, Malang Regency. Methods: This study used Fourier Transform Infrared (FT-IR) Spectroscopy and Chemometrics in data processing and used KLT Densitomestri to determine capsaicin levels in chili powder. Data processing was performed using multivariate calibration using PLS (Partial last Square) and OPLS-DA (Orthogonal Partial Least Squares Discriminant Analysis). The samples used in this study were 10 market samples, control chili powder samples, and mixed samples of chili powder with Rhodamin B synthetic dye with a concentration of 0-50% (b/b). Results: From the results of the study, it was found that the capsaicin content in chili powder was 624.77 µg/g, then the results of OPLS-DA processing of market samples 1 to 7 were estimated to be not pure chili powder and samples 8 to 10 were estimated to be pure chili powder (there was a mixture of other ingredients). Furthermore, market samples 1 to 7 were tested using PLS. From the PLS results, the best calibration model was obtained at wave numbers 1800-1180 cm-1 where the calibration value was 0.9989; RMSEC value 0.789; validation 0.9968; RMSEP 1.93. PLS results show that in samples 1 to 4 and sample 6 it is estimated that there is a counterfeiter of Rhodamin B synthetic dye while in samples 5 and 7 no synthetic dye was detected in the chili powder, possibly the material added is not from synthetic dyes. Conclusion: So it is concluded that the market chili powder samples sold in the Singosari Traditional Market have samples of pure chili powder and samples that are predicted to have counterfeiters. Keyword: Chili Powder, Rhodamine B, Chemometrics, FT-IR